Physical oceanography during BONUS INTEGRAL WINTER cruise on RV Aranda (28.02.-11.03.2019) for monitoring the wintertime ghg-gases - Heini Jalli; Milla Johansson; Pekka Kosloff; Tuomo Roine; Mika Raateoja (PANGAEA, 2021)
The dataset includes the station metadata, secchi depths and CTD (temperature, salinity and oxygen) at the water sample depths from BONUS INTEGRAL winter cruise on RV Aranda for monitoring the green-house gases and related parameters 28.02.-11.03.2019. The cruise was one of the two research cruises made within the BONUS INTEGRAL project (2017-2020): https://www.io-warnemuende.de/integral-home.html and https://www.bonusportal.org/projects/blue_baltic_2017-2020/integral. The full CTD profiles are in ICES marine database (https://www.ices.dk/data/Pages/default.aspx).